Application of the Restitution Triangle in Instruding Positive Discipline for Students - Nofitri, Fifi; Desyandri, Desyandri; Irdamurni, Irdamurni (International Journal of Educational Dynamics, 2023)
The restitution triangle is a strategy that can be applied as a process of creating conditions that guide students to correct their mistakes. In the process of the restitution triangle activity the teacher does not forget to ask about class beliefs. Class beliefs are an agreement made at the beginning of learning between teachers and students. The purpose of this study was to determine the application of the triangle of restitution in instilling positive behavior in students. The method used in this research is a literature study with a qualitative approach, the research subjects are students and teachers. We can see that with this restitution triangle students are able to solve the problems they face by finding solutions or solutions on their own.